POSITIVE USE OF ENDOPHYTIC FUNGI FOR PATHOGEN BIOCONTROL IN TOMATO CROPS (REMUNOM, 2024)
The use of endophytic fungi for biocontrol of pathogens in tomato crops is a promising alternative in the scenario of sustainable agriculture. Endophytic fungi are microorganisms that live inside plant tissues without causing damage, benefiting plants in several ways, including promoting growth, inducing systemic resistance and directly suppressing pathogens. The objective of the study was to evaluate the potential of different strains of endophytic fungi in the biocontrol of pathogens that affect tomato crops, seeking ecological alternatives to the use of chemical pesticides. The review methodology involved the careful selection of scientific articles published in renowned journals. Academic databases such as PubMed, Scopus and Web of Science were used to find relevant studies. The adoption of this practice can significantly contribute to reducing the use of chemical pesticides, promoting more sustainable and healthy agriculture. The review also points to the need for additional research to better understand plant-fungus interactions and develop efficient application protocols. Knowledge transfer between the scientific community and farmers is essential for the successful implementation of this technology in agriculture.